2017
DOI: 10.5539/ijms.v9n4p38
|View full text |Cite
|
Sign up to set email alerts
|

Show Me the Money: On Predicting Actual Purchases in Cross-National Sponsorship

Abstract: The improvements in new media technologies in conjunction with the expansion of innovative opportunities for marketing and consuming sport have played direct roles in the globalization of sport. However, those in the Sport Management academic field are still trying to understand the effect of culture on sport consumer behavior. Guided by Hofstede's cultural dimensions theory, the purpose of this study was to examine the sponsorship and cross-national relationships among the short-term/long-term orientation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 46 publications
1
2
0
Order By: Relevance
“…Namely, the results of the SEM model have shown that the attitude toward sport sponsorship has a stronger impact on purchasing decisions than the sport sponsorship perception. Also, an earlier study showed that a positive attitude towards the sponsor led to increased intention to buy its products [39]. Nassis et al [50] studied basketball fans who had a positive perception of sport sponsorship and showed they were more likely to develop positive attitudes towards sponsors and to buy their products, which is also consistent with the results obtained.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Namely, the results of the SEM model have shown that the attitude toward sport sponsorship has a stronger impact on purchasing decisions than the sport sponsorship perception. Also, an earlier study showed that a positive attitude towards the sponsor led to increased intention to buy its products [39]. Nassis et al [50] studied basketball fans who had a positive perception of sport sponsorship and showed they were more likely to develop positive attitudes towards sponsors and to buy their products, which is also consistent with the results obtained.…”
Section: Discussionsupporting
confidence: 74%
“…On the other hand, the results of a certain number of previous studies are not in line with our results. Namely, Zaharia et al [39] state that awareness of sponsorship does not significantly affect attitudes or decision making in purchasing. Also, Papdimitrou et al [51] showed that the role of sponsor or brand attitude is not important for purchase decisions of sponsors' products for three groups of respondents (volunteers, marathon participants and viewers).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation